Lightweight SOA-Based Multi-Engine Architecture for Workflow Systems in Mobile Ad Hoc Networks - Tongguang Zhang; Shuai Zhao; Bo Cheng; Maurizio Farina; Jiwei Huang; Junliang Chen; Bingfei Ren; Shoulu Hou (IEEE Access, 2018)
At present, most mainstream workflow systems adopt client/server architecture where the workflow system server (WSS) runs on a server in a fixed network or cloud and the workflow system client (WSC) runs on a PC or a mobile smart device (MSD), such as a smartphone. However, in special circumstances (e.g., battlefields, earthquakes, tsunamis, and floods) communication infrastructure can be damaged or it does not exist; consequently, traditional workflow systems cannot meet the need. MSDs are now more powerful than ever and can be used to construct mobile ad hoc networks (MANETs) in special circumstances. To provide communication using workflow technology in MANETs, we present a lightweight service-oriented architecture-based multi-engine architecture for workflow systems in MANETs. One characteristic of the architecture is that certain MSDs play dual roles, functioning as both a WSS and a WSC. We provide the architecture design details and implement the workflow engine on Linux/Android platforms. Because the multiple workflow engines must be able to cooperate closely, we present a multi-engine trigger mechanism. The test results validate the effectiveness and availability of the workflow engine and verify the feasibility of the algorithm for the multi-engine trigger mechanism.